Two women and two children - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows two women and two young girls posing outside in front of a large tree trunk. They appear to be a family. The woman in the back row is standing with her hand on the youngest of the girls. The second woman is seated in front of the first and has the older of the girls sitting in her lap. Both girls have balloons and the older one is holding her's so that the slogan "Unity and more in '84" is visible. The younger child is holding a hotdog in a napkin.